1994
DOI: 10.1007/bf02059876
|View full text |Cite
|
Sign up to set email alerts
|

Why are predator urines aversive to prey?

Abstract: Predator odors often repel prey species. In the present experiments, we investigated whether changes in the diet of a predator, the coyote (Canis latrans) would affect the repellency of its urine. Furthermore, because predator odors have a high sulfur content, reflecting large amounts of meat in the diet, we investigated the contribution of sulfurous odors to repellency. Our results were consistent with the hypothesis that diet composition and sulfurous metabolites of meat digestion are important for the repel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
1
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(150 citation statements)
references
References 23 publications
4
140
1
5
Order By: Relevance
“…Similar effects have been shown in a number of studies with other prey species: beavers, black-tailed deer, snowshoe hares, deer mice, guinea pigs, house mice, gray squirrels, meadow voles, and mountain voles during exposure to coyote, wolf, fox, and bobcat urine (Sullivan et al, 1985a(Sullivan et al, ,b, 1988Epple et al, 1993;Nolte et al, 1994;Swihart et al, 1999;Rosell, 2001), and, most relevantly, in rats during exposure to fox urine (Burwash et al, 1998;Campbell et al, 2003;Farmer-Dougan et al, 2005). The results of all these studies were confirmed here.…”
Section: Discussionsupporting
confidence: 73%
“…Similar effects have been shown in a number of studies with other prey species: beavers, black-tailed deer, snowshoe hares, deer mice, guinea pigs, house mice, gray squirrels, meadow voles, and mountain voles during exposure to coyote, wolf, fox, and bobcat urine (Sullivan et al, 1985a(Sullivan et al, ,b, 1988Epple et al, 1993;Nolte et al, 1994;Swihart et al, 1999;Rosell, 2001), and, most relevantly, in rats during exposure to fox urine (Burwash et al, 1998;Campbell et al, 2003;Farmer-Dougan et al, 2005). The results of all these studies were confirmed here.…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, it has been hypothesized that the sulphurous metabolites of meat digestion are important for the repellency of predator urine and faecal odours to potential prey (Nolte et al, 1994), and primates have been shown to actively avoid such odours (Sündermann et al, 2005). Taken together, these findings strongly support the notion that indols and thiols should be of high behavioural relevance for non-human primates.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 61%
“…These molecules are often the only warning a prey has that a predator is nearby. They include a class of heterocyclic sulfur or nitrogencontaining compounds generated by meat digestion (47). To these belongs 2,4,5-trimethylthiazoline (TMT), a component of fox (Vulpes vulpes) feces (48) that is well known for its fear-inducing properties (49, 50), (Fig.…”
Section: Alarm Pheromones and Predator Scents Sharing A Common Chemicalmentioning
confidence: 99%